Factors that influence customers satisfaction toward Air Asia services / Maizatul Syafiqah Mohd Zakidin , Nadiah Amiruddin and Siti Nur Najwa Abdullah - Mohd Zakidin, Maizatul Syafiqah; Nadiah Amiruddin, Nadiah; Abdullah, Siti Nur Najwa (Faculty of Hotel and Tourism Management, 2014)
The purpose of this study is to provide a better understanding of customer satisfaction level with the availability of the in flight food service, price and online booking after using the Air Asia airline service. The research objective of this paper is to identify factors that influence customer satisfaction towards Air Asia and to identify the relationship between price and potential customer of Air Asia. The target population of this study is among Univesiti Teknlologi MARA (UiTM) students included from peninsular Malaysia and Sabah & Sarawak. Questionnaire data collection method has been used for this study. The survey is undertaken throughout October 2013. The result revealed that the respondent was satisfied with the services provided by Air Asia Airline. It also showed the first objective of this research is fulfilling by all three factors which influences customer satisfaction towards Air Asia Airline. Furthermore, respondent had agreed that Air Asia online booking service is flexible to use, the price of Air Asia ticket is align with their service and there are a quality of in flight food been served to them.